Green School-Based Institutional Innovation at MI Assunniyyah 45 Kencong, Jember - Dukan Jauhari Faruq; Titiek Rohanah Hidayati; Erma Fatmawati (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research stems from the importance of developing an environmentally conscious school culture—one that focuses not merely on physical greening activities but also on institutional innovations capable of ensuring the sustainability of environmental programs within the madrasah (Islamic school). The Adiwiyata program, as a form of the